A holistic ecosystem based approach to ecological protection and green development the case of Huangshan in the People Republic of China. - Fan, Mingyuan (ADB Briefs., 2021)
The Anhui Huangshan Xin an River Ecological Protection and Green Development Project in the Peoples Republic of China applied innovations and pioneering management approaches in its project design. It introduced modern concepts and technologies, most notably the adoption of two results-based green financing instruments: cash grants for farmers applying improved farm management practices and equity financing for enterprises promoting green business. These funds are built on an existing ecocompensation scheme. Other measures include a sponge city and low-impact development program to manage urban stormwater pollution, and the establishment of a smart environmental, health, and safety management system platform.